PENGARUH UKURAN PEMERINTAH DAERAH, PENDAPATAN ASLI DAERAH, DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH DI KALIMANTAN SELATAN TAHUN 2019-2021 - Ernawati Ernawati; Novi Dirgantari; Hadi Pramono; Hardiyanto Wibowo (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
Local government financial performance is an achievement of local government success in managing regional finances by utilizing all available resources in their regions. The purpose of this study is to determine the effect of local government size, local original income, capital expenditure and assess the difference in the effect of mining/non-mining area PAD on local government financial performance. This type of research is quantitative research with secondary data sourced from the Examination Results Report on Local Government Financial Statements (LHP LKPD) obtained from requests for information on the BPK RI E-PPID service. The sampling method uses the total sampling/census method where the entire population is used as a sample. So that the samples in this study amounted to 39, namely 13 Regencies / Cities in South Kalimantan in 2019-2021. The analysis method used is multiple linear regression analysis. The results of this study are that the size of local government does not have a significant effect, local original income has a negative and significant effect, capital expenditure has a positive and significant effect, and dummy PAD in mining/non-mining areas has a significant negative effect on the financial performance of local governments.